2000
DOI: 10.2527/2000.78102595x
|View full text |Cite
|
Sign up to set email alerts
|

Using measurements of muscle color, pH, and electrical impedance to augment the current USDA beef quality grading standards and improve the accuracy and precision of sorting carcasses into palatability groups.

Abstract: This research was conducted to determine whether objective measures of muscle color, muscle pH, and(or) electrical impedance are useful in segregating palatable beef from unpalatable beef, and to determine whether the current USDA quality grading standards for beef carcasses could be revised to improve their effectiveness at distinguishing palatable from unpalatable beef. One hundred beef carcasses were selected from packing plants in Texas, Illinois, and Ohio to represent the full range of muscle color observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
3
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 8 publications
3
36
3
3
Order By: Relevance
“…If single-trait selection was practiced, theoretically, the accuracy of direct selection on LTL_TEND would be 0.56 compared with the indirect single-trait selection on LTL_SF, LTL_L*, and LTL_a*, which would be 0.43, 0.23 and 0.08, respectively. No other literature estimates were found for these genetic relationships; however, several studies have reported similar phenotypic or residual correlations between shear force and L* colour (Dubeski et al 1997;Wulf et al 1997;Wulf and Page 2000). Correlations between cooking loss % and other traits varied between TEMP and TROP.…”
Section: Genetic Parametersmentioning
confidence: 73%
“…If single-trait selection was practiced, theoretically, the accuracy of direct selection on LTL_TEND would be 0.56 compared with the indirect single-trait selection on LTL_SF, LTL_L*, and LTL_a*, which would be 0.43, 0.23 and 0.08, respectively. No other literature estimates were found for these genetic relationships; however, several studies have reported similar phenotypic or residual correlations between shear force and L* colour (Dubeski et al 1997;Wulf et al 1997;Wulf and Page 2000). Correlations between cooking loss % and other traits varied between TEMP and TROP.…”
Section: Genetic Parametersmentioning
confidence: 73%
“…Steaks from Canada AA carcasses, however, with a mean WBSF value of about 4.0 kg when converted from Newtons to kg (1 kg = 9.8066 N) would be considered unacceptably tough if measured against the tenderness thresholds of 34 N (3.5 kg) of Wulf et al (1998) or the 37.95 N (3.87 kg) of Rodas-González et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated how VIA can supplement the visual USDA carcass grading system for assignment of yield grade, (Belk, Scanga, Tatum, Wise, & Smith, 1998;Cannell et al, 1999Cannell et al, , 2002Steiner et al, 2003;Wulf & Page, 2000;Wyle et al, 2003) and quality grade (Wulf & Page, 2000;Wyle et al, 2003). Some of these integrated approaches have resulted in commercial developments as outlined in Section 3.5.…”
Section: Augmenting Usda Gradingmentioning
confidence: 98%